Clinical Outcomes of Symptomatic Neuroma Resection and Reconstruction with Processed Nerve Allograft. Issue 10 (4th October 2021) - Jain, Sonu A.; Nydick, Jason; Leversedge, Fraser; Power, Dominic; Styron, Joseph; Safa, Bauback; Buncke, Gregory
Abstract : Background: Neuromas causing sensory disturbance can substantially affect nerve function and quality of life. Historically, passive termination of the nerve end and proximal relocation to muscle or bone has been performed after neuroma resection, but this method does not allow for neurologic recovery or prevent recurrent neuromas. The use of processed nerve allografts (PNAs) for intercalary reconstruction of nerve defects following neuroma resection is reasonable for neuroma management, although reported outcomes are limited. The purpose of this study was to assess the outcomes of pain reduction and functional recovery following neuroma resection and intercalary nerve reconstruction using PNA. Methods: Data on outcomes of PNA use for peripheral nerve reconstruction were collected from a multicenter registry study. The registry database was queried for upper extremity nerve reconstruction with PNA after resection of symptomatic neuroma. Patients completing both pain and quantitative sensory assessments were included in the analysis. Improvement in pain-related symptoms was determined via patient self-reported outcomes and/or the visual analog scale. Meaningful sensory recovery was defined as a score of at least S3 on the Medical Research Council Classification scale. Results: Twenty-five repairs involving 21 patients were included in this study. The median interval from injury to reconstruction was 386 days, and the average nerve defect length was 31 mm. Pain improved in 80% of repairs. Meaningful sensory recovery was achieved in 88% of repairs. Conclusion: Neuroma resection and nerve reconstruction using PNA can reduce or eliminate chronic peripheral nerve pain and provide meaningful sensory recovery.